Micro Learning Media for Teaching English at Junior High School Students - Putu Kerti Nitiasih; Made Hery Santosa; Putu Suarcaya; Gede Ratnaya (Universitas Pendidikan Ganesha, 2023)
The students’ lacked of interest in learning English at Junior High School tended to cause of having short memory on the material being explained. Micro-learning is a tiny activity by teachers and learners in the classroom, to help the students’ short memory. This means that teachers need to provide a bit-sized learning material to help students to maintain their memories. Based on the phenomena developing video materials using the micro-learning concept is badly needed. The aim of this study is to develop micro learning media for teaching English at junior high school students. The micro-learning video developed in this research are combined with three teaching model namely; problem-based learning, project-based learning and discovery-based learning. The effectiveness of the developed video materials for the learners at junior high school was evaluated using criteria of a good English material suggested by the formula. Moreover, the checklist consisted 5 scales of scoring they are; 5 represents excellent, 4 represents good, 3 represents average, 2 represents below average, and 1 represents poor. The result showed that the quality of the developed micro-learning-based video materials implemented at junior high school was good. Thus, the micro-learning based video materials were good to help the students at junior high school to sustain their memories in learning English.